2015
DOI: 10.2105/ajph.2014.302345
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effects of a Complementary Parent Intervention and Prior Exposure to a Preadolescent Program of HIV Risk Reduction for Mid-Adolescents

Abstract: Preadolescents and mid-adolescents in HIV-affected countries should receive HIV prevention interventions that include parental participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
(14 reference statements)
3
14
0
Order By: Relevance
“…As previously reported [6], through 18 months follow-up among these FOYC-naïve youth, compared to HFLE-ONLY youth, BFOOY-CImPACT youth consistently exhibited significantly higher condom-use skills and HIV/AIDS knowledge; BFOOY-GFI and BFOOY-ONLY youth performed better in these tasks on one or more occasions. In the present analysis, at 24 months, condom-use skills remained significantly higher for the BFOOY-CImPACT and BFOOY-ONLY youth [ F (6,1163)=8.80,p<0.01].…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…As previously reported [6], through 18 months follow-up among these FOYC-naïve youth, compared to HFLE-ONLY youth, BFOOY-CImPACT youth consistently exhibited significantly higher condom-use skills and HIV/AIDS knowledge; BFOOY-GFI and BFOOY-ONLY youth performed better in these tasks on one or more occasions. In the present analysis, at 24 months, condom-use skills remained significantly higher for the BFOOY-CImPACT and BFOOY-ONLY youth [ F (6,1163)=8.80,p<0.01].…”
Section: Resultssupporting
confidence: 78%
“…Receipt of BFOOY in grade-10 has previously been shown to result in improvements in condom-use skills, condom-use efficacy and HIV knowledge at six months and some continued benefits at 12 and 18 months [6]. The current results show the inclusion of the parent intervention (CImPACT) sustained condom use skills through the 24 month follow-up period.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Our analysis measured attitudes toward sexual risk-taking rather than sexual behaviors since prior research with this population indicated low rates of sexual activity (Ssewamala, Han, et al, 2010). However, the transitional period from adolescence to young adulthood is one of the riskiest periods for HIV acquisition (Patton et al, 2010; Stanton et al, 2015). Motivating orphaned adolescents to avoid HIV through ongoing engagement both prior to and at the start of sexual activity will be crucial.…”
Section: Discussionmentioning
confidence: 99%
“…(15,16) For effectiveness of health education actions, the health professionals need to recognize the autonomy, assimilation capacity, and previous knowledge of adolescents, through dialogue, respect, and shar-ing of knowledge, using the elements as proposed by the adolescents. (16) References that may identify the adolescents' sexual life, such as naming the educational intervention with titles associated with sexuality, can generate feelings of rejection and resistance to participate in the educational moment.…”
Section: Discussionmentioning
confidence: 99%